Interdisciplinary Approach in Management of Secondary Occlusal Trauma: A Case Report with a 2-Year Follow-up - Francis, Delfin L.; Reddy, Saravanan S.P.; Pradhan, Shaili (European Journal of General Dentistry, 2025)
Secondary occlusal trauma in periodontally compromised patients can accelerate attachment loss and complicate management. The combination of substantial periodontal disease and secondary occlusal stress in adults leads to a progressive loss of attachment and bone. If not subjected to appropriate intervention, this condition possesses the capacity to significantly impact the predicted outcome. This case report outlines a comprehensive interdisciplinary strategy employed for localized periodontitis with secondary occlusal trauma. A 40-year-old woman presented with localized periodontitis in mandibular incisors, pathologic migration, thin gingival phenotype, and inadequate keratinized tissue. After initial nonsurgical therapy, orthodontic realignment was performed to correct traumatic occlusion, followed by autologous soft tissue grafting for phenotype modification. After the completion of the initial periodontal therapy, fixed orthodontic treatment was initiated. Soft tissue grafting was employed to enhance the gingival phenotype. Over a 2-year follow-up, clinical attachment improved from 6 to 3 mm, keratinized tissue increased from 1 to 6 mm, and recession height reduced from 5 to 2 mm. Creeping attachment was observed after 1 year. Patient-reported outcomes included improved oral hygiene and reduced anxiety. Furthermore, there was a notable improvement in self-performed plaque control, which was a significant measure reported by the patient. The use of an interdisciplinary strategy was crucial for the efficient management of the potential exacerbation of periodontal disease caused by secondary occlusal trauma. The implementation of post-orthodontic periodontal treatment had the potential to result in significant enhancements in the periodontal phenotype, and hence the achievement of successful self-performed plaque control. An interdisciplinary sequence of orthodontic correction and phenotype modification stabilized traumatized anterior teeth and enhanced gingival phenotype, resulting in durable functional and aesthetic outcomes.
Keywords: case report; interdisciplinary; orthodontic; periodontal